Cell adhesion in free-standing multilayer films made of chitosan and alginate - Caridade, S. G. (2012)
The method for preparing multilayer ultrathin films by the consecu- tive deposition of oppositely charged polyelectrolytes has gained tre- mendous recognition due the user friendly preparation, capability of incorporating high loads of different types of biomolecules in the films, fine control over the materials’ structure, and robustness of the products under ambient and physiological conditions. However the preparation of such films needs the assembly on a substrate and, sometimes, cannot be detached from it, which has limited the appli- cation of such films in areas as tissue engineering and regenerative medicine (TERM).Thus, the production of free-standing films is of extreme importance once it allows the direct experimental determi- nation of many physical properties of fundamental significance such as ion permeation and mechanical properties that can be tuned for real-world applications. In this work, we investigated the elaboration of free-standing multilayer films made of chitosan (CHI) and alginate (ALG), by detaching a polyelectrolyte multilayer film from its under- lying substrate without any postprocessing step. The conditions for optimized film growth were investigated. The adhesion of C2C12 myoblast cells on the CHI/ALG membrane was assessed by cytoskele- tal and nuclear staining. A good cell adhesion and spreading was observed all over the surface. The results demonstrate the potential of such biocompatible free standing membranes made of CHI and ALG for applications in TERM.